Multifunctional Tannins from Phyllanthus amarus Exhibit Disease-Modifying Activities Against Alzheimer’s Pathogenesis: An In Vitro and In Vivo Investigation - Rahul P. Pol; Laxmikant M. Purane; S. R. Kane; A. A. Misal; Akshay R. Yadav; Atul R. Chopade; S. M. Sarvagod; P. D. Jadhav (International Journal of Pharmacy and Analytical Research, 2026)
Alzheimer’s disease (AD) manifests as a chronic neurodegenerative syndrome featuring cognitive impairment alongside characteristic neuropathological markers: amyloid-beta (Aβ) plaques and tau-associated neurofibrillary tangles. Absence of curative interventions necessitates exploration of novel therapeutic candidates. Phyllanthus amarus, recognized for its phytochemical diversity including tannins and lignans, demonstrates antioxidant and neuroprotective bioactivities warranting AD-focused investigation. This investigation employed systematic extraction and characterization of tannins from Phyllanthus amarus, subsequently evaluating their anti-Alzheimer properties through cellular and transgenic animal models. Experimental data revealed substantial neuroprotective effects, including suppression of Aβ aggregation and mitigation of neuroinflammatory processes. Behavioral studies in AD-model mice demonstrated cognitive function restoration following tannin administration. Molecular analyses identified modulation of key pathological pathways, specifically amyloid precursor protein processing regulation and oxidative stress amelioration. Findings validate Phyllanthus amarus tannins as promising disease-modifying candidates for Alzheimer’s therapy. This research strengthens the scientific rationale for phytochemical-based neurotherapeutic development, presenting viable strategies for addressing neurodegenerative conditions.